1982
DOI: 10.1016/s0022-328x(00)89067-1
|View full text |Cite
|
Sign up to set email alerts
|

ansa-Metallocene Derivatives

Abstract: A synthesis for racemic ethylene-bis(4,5,6, 7-tetrahydro-l-indenyl)titanium dichloride is described. The molecular structures of this compound, of its mesoisomer and of a binaphtholate complex of the (S,S)-enantiomer have been determined. Cleavage of this binaphtholate complex gives the pure (S,8)enantiomer. * For part III. see l'cf. 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
200
0
10

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(215 citation statements)
references
References 11 publications
5
200
0
10
Order By: Relevance
“…The Brintzinger-type C 2 -chiral titanocene catalysts 127 efficiently promote asymmetric hydrogenation of imines (Figure 1.30). 128,129 A variety of cyclic and acyclic imines are reduced with excellent enantioselectivity by using these catalysts.…”
Section: Reduction Of Iminesmentioning
confidence: 99%
“…The Brintzinger-type C 2 -chiral titanocene catalysts 127 efficiently promote asymmetric hydrogenation of imines (Figure 1.30). 128,129 A variety of cyclic and acyclic imines are reduced with excellent enantioselectivity by using these catalysts.…”
Section: Reduction Of Iminesmentioning
confidence: 99%
“…According to well-known procedures for the resolution of titanium metallocenes, [14][15][16][17][18] we carried out the reaction of one equivalent of sodium bi- Scheme 1. naphtholate with 1 in THF at room temperature to afford the desired titanocene binaphtholate phosphane 7. However, a careful study of the 1 H NMR spectrum of the crude product revealed that a partial loss of the Cp(CH 2 ) 2 PPh 2 moiety occurs in this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…of dibromoethane in THF, subsequent workup and purification by crystallization (Scheme 19). In contrast to bis(indenyl)ethane for which the 3,3Ј-indenyl-bridged isomer predominates, [10,66,118] all siloxy-substituted indenes yield exclusively the 1,1Ј-bridged product. [85,90,93,106] Only in the case of the six-membered ring substituted 2-siloxyindenes 69 [91] and 70 [106] were the yields for the ethylene-bridged bis(indenyl) ligands 79 and 80 ( Figure 10) low (4.8 and 3.9%, respectively), which resulted from the nearly exclusive predomination of the spirocyclopropane adducts formed by intramolecular bis(alkylation) reactions of the substituted indene.…”
mentioning
confidence: 88%